2015
DOI: 10.4236/as.2015.61003
|View full text |Cite
|
Sign up to set email alerts
|

Differential Susceptibility of <i>Conyza bonariensis</i> Biotypes to Glyphosate and ALS-Inhibiting Herbicides in Argentina

Abstract: The aim of this study was to compare control of three stages biotypes (rosette, bolting, and reproductive stage) of Conyza bonariensis glyphosate susceptible biotype (S) and tolerant biotype (T) to glyphosate with glyphosate and mixtures of acetolactate synthase (ALS)-inhibiting. For glyphosate, the dose-response curves confirmed that injury of the biotype T relative to biotype S was significantly lower for both rosette and bolting stages. Resistance index (RI) for this herbicide was approximately 4 for both w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 29 publications
(33 reference statements)
1
6
0
2
Order By: Relevance
“…The doses used in our research (960 g ha -1 for glyphosate and 20 g ha -1 for chlorimuron) have shown to be able to discriminate S and R populations in the three Conyza spp. species (Kruger et al 2009, Santos et al 2014a, Puricelli et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…The doses used in our research (960 g ha -1 for glyphosate and 20 g ha -1 for chlorimuron) have shown to be able to discriminate S and R populations in the three Conyza spp. species (Kruger et al 2009, Santos et al 2014a, Puricelli et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Both cohorts were controlled easily under conventional tillage: the autumn cohort was killed by the tillage operation, whereas the spring cohort was either prevented germinating by mechanical burial or chemically controlled upon germination during establishment of the summer crop. However, the absence of tillage operations allows survival of the autumn cohort, which turned out to be extremely difficult to control chemically in spring during seedbed preparation prior to sowing the summer crop, particularly when plants have grown large enough to tolerate commonly applied herbicide doses …”
Section: Seed Dormancy As a Trait For Adjustment: Stories Of Evolutiomentioning
confidence: 99%
“…However, the absence of tillage operations allows survival of the autumn cohort, which turned out to be extremely difficult to control chemically in spring during seedbed preparation prior to sowing the summer crop, particularly when plants have grown large enough to tolerate commonly applied herbicide doses. 21 A good example of plasticity in a dormancy strategy can be found in Polygonum aviculare (prostrate knotweed). Seeds from this summer annual weed are dispersed with high dormancy at the end of the summer and become buried easily due to their small size.…”
Section: Seed Dormancy As a Trait For Adjustment: Stories Of Evolutiomentioning
confidence: 99%
“…Trabajos realizados demuestran que la sensibilidad de rama negra a los tratamientos químicos es condicionada por el tamaño de las plantas, las dosis y el momento de aplicación (Nisensohn, Tuesca y Papa, 2011;Gianelli et al, 2015;Puricelli et al, 2015); por lo cual es necesario conocer los patrones de emergencia de esta maleza en cada región para determinar el momento oportuno de control.…”
Section: Introductionunclassified
“…A su vez, en Argentina se han desarrollado numerosos estudios que destacan la importancia de un control temprano de Conyza spp. en estadio de roseta y menor a 15 cm de altura durante el barbecho químico (Metzler, Puricelli y Papa, 2013;Ustarroz y Cerutti, 2015;Gianelli et al, 2015;Puricelli et al, 2015;Kahl 2016). En este sentido, la variación en tamaño y desarrollo de las plantas ocasionada por la competencia intraespecífica podría afectar la efectividad de las dosis de los tratamientos químicos utilizados para su control.…”
Section: Introductionunclassified